Análise da ação terapêutica dos ácidos oleanólico e ursólico na leishmaniose visceral experimental - Jesus, Jessica Adriana de [UNIFESP] (2015)
This study aimed to evaluate the in vitro action of two triterpenes, oleanolic acid (OA) and ursolic (UA) on promastigote and / or amastigote forms of L. (L.) chagasi and the therapeutic potential of UA in L. (L.) chagasi - chronically infected hamsters as well as the toxicity of the UA in healthy hamsters. These triterpenes were commercially obtained, and characterized by nuclear magnetic resonance (1H and 13C NMR). In the in vitro experiments, promastigotes were incubated with OA, UA and amphotericin B (positive control) and the Effective Concentration 50% (EC50) was determined. Ultrastructural studies and fixation with annexin V and propidium iodide were carried out in UA-treated promastigotes. The potential of this triterpene was also evaluated in intracellular amastigotes of L. (L.) chagasi. To evaluate the therapeutic potential of UA, L. (L.) chagasi - chronically hamster were treated daily during 16 days with 1.0; 2.0 mg/kg UA, and 5.0 mg/kg of amphotericin B (intraperitoneal route). After 15 days of the last dose, the parasitism of the spleen and liver was measured, as well as the proliferation of splenic mononuclear cells and the expression of IFN-?, IL-10 and IL-4. Humoral immune response was evaluated in the serum of animals. Histopathological changes were also analyzed in spleen and liver. To evaluate the toxicity of UA and amphotericin B, healthy hamsters were treated with the same doses of compounds, and histological analysis of spleen, liver, kidney, lung and heart as well as biochemical changes were made. In vitro studies showed that the UA present leishmanicidal activity, eliminating promastigotes with EC50 of 1.8 ug/mL, but did not eliminate OA-treated parasites, possibly due to their structural difference in the molecules (position of the methyl group). UA reduced the infection index of macrophages infected by 62% when treated with 10 ug/mL UA. Ultrastructural analysis suggested that promastigote forms incubated with UA eliminated parasites by programmed cell death. In vivo studies showed that the animals treated with 1.0 and 2.0 mg / kg of UA had lesser parasitism in spleen (41.6 and 35.8% respectively) and liver (84.97, 71.31% respectively) compared with the infected group and liver compared to the infected group and histologically these animals showed preservation of red and white pulp, which correlate with high rate of proliferation of splenic mononuclear cells, and the populations of clones belonging to Th1 and Th2 type. Ex vivo experiments have demonstrated that the immune response of animals treated with amphotericin B and UA was associated to a response mediated by IFN-? and IL-10. Possibly IL-10 has a role in the persistence of parasite in spleen and liver of treated animals. Moreover, it was seen that the treatment with UA does not lead to amplification of both MRPA and PTR1 genes, that have an important role in drug resistance, however animals treated with amphotericin B had parasites with amplified genes. These data indicate that UA may be an interesting natural compound for the development of new classes of drugs against visceral leishmaniasis, since their effects in vitro and in vivo were comparable to those of amphotericin B.